Regulation of Inflammation Pathways and Inflammasome by Sex Steroid Hormones in Endometriosis - García-Gómez, Elizabeth; Vázquez-Martínez, Edgar Ricardo; Reyes-Mayoral, Christian; Cruz-Orozco, Oliver Paul; Camacho-Arroyo, Ignacio; Cerbón, Marco (Frontiers in Endocrinology, 2020)
Endometriosis is a gynecological disorder characterized by the growth of endometrial tissue (glands and stroma) outside the uterus, mainly in the peritoneal cavity, ovaries, and intestines. This condition shows estrogen dependency and progesterone resistance, and it has been associated with chronic inflammation, severe pain, and infertility, which negatively affect the quality of life in reproductive women. The molecular mechanisms involved in the pathogenesis of endometriosis are not completely understood; however, inflammation plays a key role in the pathophysiology of the disease, mainly by altering the function of immune cells (macrophages, natural killer, and T cells) and increasing levels of pro-inflammatory mediators in the peritoneal cavity, endometrium, and blood. These immune alterations inhibit apoptotic pathways and promote adhesion and proliferation of endometriotic cells, as well as angiogenesis and neurogenesis in endometriotic lesions. It has been demonstrated that hormonal alterations in endometriosis are related to the inflammatory unbalance in this disease. Particularly, steroid hormones (mainly estradiol) promote the expression and release of pro-inflammatory factors. Excessive inflammation in endometriosis contributes to changes of hormonal regulation by modulating sex steroid receptors expression and increasing aromatase activity. In addition, dysregulation of the inflammasome pathway, mediated by an alteration of cellular responses to steroid hormones, participates in disease progression through preventing cell death, promoting adhesion, invasion, and cell proliferation. Furthermore, inflammation is involved in endometriosis-associated infertility, which alters endometrium receptivity by impairing biochemical responses and decidualization. The purpose of this review is to present current research about the role of inflammasome in the pathogenesis of endometriosis as well as the molecular role of sex hormones in the inflammatory responses in endometriosis.